Penyusunan Laporan Keuangan dan SPT Tahunan Wajib Pajak UMKM - Nandiroh, Umi; Hidayati, Irma; Badria, Nuril (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
The low tax compliance of MSMEs is due to tax policies that are too burdensome for them. Tax regulations are burdensome for MSMEs, thus affecting the growth of this sector. Facts on the ground show that MSME actors often feel bothered by the applicable tax provisions. Starting from the complexity of tax administration, which must be passed in carrying out tax obligations. Plus the low competence of SMEs in preparing financial reports, as a basis for calculating taxes, and attachments in reporting Annual Tax Returns (Annual SPT). This is the reason behind the existence of this service activity. The aim is to conduct socialization, training, and assistance to MSME actors in compiling financial reports and reporting Annual SPTs. Where this service is carried out in the MSME community in the Blimbing sub-district, Malang City. This activity lasts for 3 months, from January to March 2022. The stages carried out are in the form of socialization, training in the preparation of MSME financial reports, and SPT Reporting Assistance. This service activity has succeeded in increasing MSME tax compliance. And MSMEs who are participants in this activity feel very helpful, in compiling financial reports, as controls in financial management, and reporting SPT.